Analysis Study of the Implementation of Special Programs for Indonesian Sign Language and Oral Communication for Deaf Students - Utami, Yuni Tanjung; Rochyadi, Endang; Aprilia, Imas Diana; Rakhmat, Cece (Universitas Negeri Malang, 2025)
The purpose of this study was to obtain data that provides an overview of how the special Indonesian Sign Language System and oral communication program is implemented in special needs school classes. This study used a descriptive research design with a qualitative approach. In the data collection process, the researchers chose the instruments of interviews, observation, documentation, and questionnaires. Data analysis researchers used the data analysis model of Miles and Huberman in Sugiyono (2017), which consists of three stages: data reduction, data presentation, and conclusion drawing. The results of the study indicate that the description of the implementation of the special Indonesian Sign Language System and oral communication program for deaf students begins with assessment activities and follows up. In the planning stage, teachers prepare assessment instruments, then develop lesson plans, provide learning media, tools, and places. The implementation process is carried out based on the lesson plan that has been made and the sequence of materials that have been designed. Activities are not only in the classroom, but also outside the classroom. Follow-up in the form of discussions and delivery of progress by teachers to parents of students.